Neenakost po spolu v Sloveniji od 1993 do 2007 - Penner, Andrew M. (Teorija in praksa, 2012)
We use matched employer-employee data to examine gender differences in pay over a 15-year period (1993-2007) in Slovenia to understand how labour market stratification may be impacted by systemic economic change. The central finding of our analysis is that there was a substantial increase in gender inequality over this period, and that the organisation of gender inequality changed as well. In the period from 1993-1997, both the overall gender pay gap and the within-job wage gap were roughly 15 percent, but by 2003-2007 men on average earned roughly 23 percent more than women, and 18 percent more than women doing the same work for the same employer. Further, we show that women doing the same work for the same employer earn significantly less even in the public sector, where we had expected to find less gender inequality. We conclude by discussing the implications of our findings for understanding gender inequality in Slovenia and the kinds of policies that might serve to ameliorate these differences.
Keywords: Gender inequality; Spolna neenakost; Trg dela; Labor market; Plače; Wages; Slovenia; Slovenija; trg delovne sile; spolna diskriminacija